O4-S1.01 Rapid array-based multilocus genotyping of Chlamydia trachomatis: the easy and economical alternative. (10th July 2011) - Herrmann, B; Christerson, L; Ruettger, A; Gravningen, K; Ehricht, R; Sachse, K
Abstract : Background: Genotyping of Chlamydia trachomatis (C.) is an important technique to understand its epidemiology. Methods such as DNA sequencing of the ompA gene or multilocus sequence typing (MLST), either offer limited epidemiological resolution, or are laborious and expensive, or both. Here we present a microarray-based method for genotyping of C trachomatis . Methods: The database for our high-resolution MLST system (http://mlstdb.bmc.uu.se/ ) was used to design a multilocus typing (MLT) DNA microarray based on the ArrayStrip format (Alere Technologies, Jena, Germany). In total, the present MLT array version includes 210 different oligonucleotide probes covering the discriminatory variation in the highly variable, but stable, MLST target regions (hctB, CT058, CT144, CT172 and pbpB), as well as 61 probes for ompA. Validation of the array was done by examining 80 clinical C. trachomtis specimens from unselected adolescents and compare with results from MLST and ompA-based serotyping. Results: Successful typing was achieved for 78 (97%) of the specimens. Processing of the obtained hybridisation patterns resulted in 17 different MLT array groups, whereas sequence-based examination led to 19 MLST genotypes and seven ompA genotypes. Thus, the MLT microarray assay provided 2.4 times higher resolution than ompA and separated the commonly predominating ompA E/Bour genotype into seven genotypes. The MLT array showed 100% specificity. Compared to MLST analysis, the equipment needed for the MLT array is about 75% cheaper, consumables are 50% cheaper, analysis can be completed within one working day, instead of 3–4 days, and data analysis is easily conducted in high troughput conditions using up to 96 wells, while the practical operations are easy-to-handle and do not require specially trained personnel. Conclusion: This novel MLT array is a promising alternative for high resolution and high throughput typing of C. trachomatis and will facilitate molecular epidemiology studies of chlamydia infections.